2011
DOI: 10.1785/0120100208
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Seismic Hazard Assessment at the Eastern Caribbean Islands

Abstract: A probabilistic seismic hazard analysis has been performed to compute probabilistic seismic hazard maps for the eastern Caribbean region (10°N-19°N, 59°W-64°W), which includes in the north the Leeward Islands (from Anguilla to Dominica) and in the south the Windward Islands (from Martinique to Grenada), Barbados, Trinidad, and Tobago. The analysis has been conducted using a standard logic-tree approach that allowed systematically taking into account the model-based (i.e., epistemic) uncertainty and its influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 63 publications
0
24
0
7
Order By: Relevance
“…Similar methods were adopted by Iyengar and Ghosh (2004) and Raghu Kanth and Iyengar (2006) for the seismic hazard analysis of Delhi and Mumbai, respectively. In a very recent work, Bozzoni et al (2011) used the same criterion to assign maximum magnitude to a regional source zone. The usual trend is to use M max estimated for the source zone and assign it to all linear sources in that zone.…”
Section: Evaluation Of Seismicity Parametersmentioning
confidence: 99%
“…Similar methods were adopted by Iyengar and Ghosh (2004) and Raghu Kanth and Iyengar (2006) for the seismic hazard analysis of Delhi and Mumbai, respectively. In a very recent work, Bozzoni et al (2011) used the same criterion to assign maximum magnitude to a regional source zone. The usual trend is to use M max estimated for the source zone and assign it to all linear sources in that zone.…”
Section: Evaluation Of Seismicity Parametersmentioning
confidence: 99%
“…The level of hazard prescribed by this research is substantially larger than previous works (i.e., Bozzoni et al [3] suggest 0.22 g for 475 years RP), this increment is attributed to two reasons: (1) Former works did not consider the possibility of megathrust earthquakes beneath Barbados, in fact the maximum magnitudes considered in previous works used for this zone yields 7.0-7.5 based solely on 500 year of earthquake history, much lower than the maximum magnitudes employed in this work: a M 8.0 within the exponential G-R relationship and the characteristic earthquakes within the magnitude range of M 8.3 to 9.0 based on slip rates; (2) only the classical method of Cornell-McGuire was taken into account in the computation of the disaggregation process for this work; the authors did not introduce in the logic tree formulation the free-zone method proposed by Woo [46] and used by Bozzoni et al [3] as well, it has been observed that the free zone methods yield lower hazards results than the classical Cornell method in areas of sparse seismicity in terms of short period components of ground motion [47,48].…”
Section: Discussionmentioning
confidence: 57%
“…The authors employed the earthquake catalogue and the Gutenberg Richter relationships (Table 1) developed by Bozzoni et al [3]. Fig.…”
Section: Seismotectonic Setting and Geometrical Delimitationsmentioning
confidence: 99%
See 2 more Smart Citations